Advances in Artificial Life, ECAL 2013 2013
DOI: 10.7551/978-0-262-31709-2-ch017
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Rule Compaction Strategies for Global Knowledge Discovery in a Supervised Learning Classifier System

Abstract: Michigan-style learning classifier systems have availed themselves as a promising modeling and data mining strategy for bioinformaticists seeking to connect predictive variables with disease phenotypes. The resulting 'model' learned by these algorithms is comprised of an entire population of rules, some of which will inevitably be redundant or poor predictors. Rule compaction is a post-processing strategy for consolidating this rule population with the goal of improving interpretation and knowledge discovery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 16 publications
0
37
0
Order By: Relevance
“…Previously, we demonstrated that UCS yielded the most promising performance on these types of simulated datsets when compared to XCS, MCS, GALE and GAssist (LCS algorithms) [5,6]. Therefore we utilize the 'core' version of UCS used in [7,9,10] as the standard of comparison for ExSTraCS. Notice that in Table 1 the 'core' ExSTraCS p-values are from a comparison to 'core' UCS, while all other p-values correspond to comparisons between 'core' ExSTraCS and ExSTraCS with respective mechanisms activated.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Previously, we demonstrated that UCS yielded the most promising performance on these types of simulated datsets when compared to XCS, MCS, GALE and GAssist (LCS algorithms) [5,6]. Therefore we utilize the 'core' version of UCS used in [7,9,10] as the standard of comparison for ExSTraCS. Notice that in Table 1 the 'core' ExSTraCS p-values are from a comparison to 'core' UCS, while all other p-values correspond to comparisons between 'core' ExSTraCS and ExSTraCS with respective mechanisms activated.…”
Section: Resultsmentioning
confidence: 97%
“…Discrete attribute SNP datasets very similar to those used in [7,9,10] were simulated using GAMETES [18] with; architectures at maximum and minimum detection difficulty, heritabilities (i.e. the proportion of class variance that can be attributed to modeled attributes) of (0.1, 0.2, or 0.4), a minor allele frequency of 0.2, 20 attributes (only four of which were predictive and 16 were noise), sample sizes of (200, 400, 800, or 1600) and a heterogeneous mix ratio of either (50:50 or 75:25) (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ExSTraCS 2.0 has been expanded and adapted to better suit the needs of real-world supervised learning problems wherein effective and efficient classification, prediction, data mining, and/or knowledge discovery is the goal. The features of ExSTraCS 2.0 that most differentiate it from XCS [20] or UCS [2] include: a rule specificity limit to address scalability issues [18], built-in rapid expert knowledge (EK) generation algorithms [14], EK guided covering and mutation for efficient learning and scalability [15,18], attribute tracking and feedback for reusing useful attribute combinations and characterizing patterns of heterogeneity [12], built-in rule compaction strategies [9], and the consolidation of explore/exploit to perform both simultaneously [13]. For a detailed description of the ExSTraCS 2.0 algorithm see [18].…”
Section: Exstracs 20mentioning
confidence: 99%